2019
DOI: 10.20546/ijcmas.2019.804.050
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Heritability Studies in the Recombinant Inbred Lines (F8) of Langulmota/Sambamahsuri Derivatives of Rice (Oryza sativa L.)

Abstract: 60% of the caloric intake of the three billion Asians (Guyer et al., 1998). It is primarily a high energy or high caloric food containing around 78.2% carbohydrates, 6.8% protein.Research efforts focused on development of high-yielding varieties and adoption of modern production technologies resulted in enhanced production leading to selfsufficiency in the country. Along with yield, grain and nutritional quality has also become a primary consideration in rice breeding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The estimates of simple correlation coefficients (phenotypic and genotypic) computed between eight characters under study are presented in In the present study, grain yield per plant possessed positive and highly significant correlation with number of filled grains per panicle (rp= 0.657**; rg= 0.665), spikelet fertility (rp= 0.301**; rg= 0.321), number of productive tillers per hill (rp= 0.153**; rg= 0.068), panicle length (rp= 0.133**, rg= 0.114). These findings were also corroborated by Ekka et al (2011) [5] , Lakshmi et al (2014) [11] , Hossain et al (2015) [8] , Babu et al (2012) [3] , Anis et al, (2016) [1] , Kumar et al (2018) [10] , Swapnil et al (2020) [14] , Parimala et al (2020) [12] and Khan et al (2020) [9] . It indicated that grain yield can be increased whenever there is an increase in characters that showed positive and significant association with grain yield.…”
Section: Resultsmentioning
confidence: 57%
“…The estimates of simple correlation coefficients (phenotypic and genotypic) computed between eight characters under study are presented in In the present study, grain yield per plant possessed positive and highly significant correlation with number of filled grains per panicle (rp= 0.657**; rg= 0.665), spikelet fertility (rp= 0.301**; rg= 0.321), number of productive tillers per hill (rp= 0.153**; rg= 0.068), panicle length (rp= 0.133**, rg= 0.114). These findings were also corroborated by Ekka et al (2011) [5] , Lakshmi et al (2014) [11] , Hossain et al (2015) [8] , Babu et al (2012) [3] , Anis et al, (2016) [1] , Kumar et al (2018) [10] , Swapnil et al (2020) [14] , Parimala et al (2020) [12] and Khan et al (2020) [9] . It indicated that grain yield can be increased whenever there is an increase in characters that showed positive and significant association with grain yield.…”
Section: Resultsmentioning
confidence: 57%